THEORETICAL FUNDAMENTALS OF THE AIRPORT NETWORK ANALYSIS - Марінцева, К. В. (Science-based technologies, 2013)
The methodological approaches to the analysis of airports network on the theory of complex networks based are described. Results of experimental calculations on a fragment of airports network of Ukraine are presented. Indicators of complex networks (node degree, the strength of the node, the clustering coefficient) are estimated for Ukrainian airports net fragment. Results of research explain the vision that air-transport network of all Ukrainian airports formed on basis of the feeder carrier business model for European airlines. On the selected fragment of airports network of Ukraine the most node strength have the airports in Kyiv (3861) and Odessa (1141), the degree of the node at these airports is 14 and 9, respectively. The highest clustering coefficient has Donetsk airport – 0.6. It is also made a conclusion about the low integration of Kyiv in the European network of hubs.